2018
DOI: 10.1016/j.ptsp.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

How to manage patellofemoral pain – Understanding the multifactorial nature and treatment options

Abstract: Patellofemoral pain (PFP) is one of the most prevalent conditions within sports medicine, orthopaedic and general practice settings. Long-term treatment outcomes are poor, with estimates that more than 50% of people with the condition will report symptoms beyond 5 years following diagnosis. Additionally, emerging evidence indicates that PFP may be on a continuum with patellofemoral osteoarthritis. Consensus of world leading clinicians and academics highlights the potential benefit of delivering tailored interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 134 publications
(189 reference statements)
1
46
0
2
Order By: Relevance
“…Patellofemoral pain (PFP) represents a common condition observed in orthopedic practice characterized by diffuse peripatellar and retropatellar pain [ 1 ]. PFP has an annual prevalence of 22.7% in the general population [ 2 , 3 ], affecting mainly physically active young women which are 2.23 times more prone to develop PFP as compared to men [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patellofemoral pain (PFP) represents a common condition observed in orthopedic practice characterized by diffuse peripatellar and retropatellar pain [ 1 ]. PFP has an annual prevalence of 22.7% in the general population [ 2 , 3 ], affecting mainly physically active young women which are 2.23 times more prone to develop PFP as compared to men [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings demonstrate that adolescent athletes with PFP presented poorer functional status than physically active non-athletes in almost all KOOS 0 dimensions, except for ADL. This finding may suggest that managing training loads according to symptoms could be an important issue to be considered by clinicians responsible for sports teams to reduce symptom aggravation of adolescent athletes with PFP (Lack, Neal, De Oliveira Silva, & Barton, 2018). Accordingly, Rathleff, Roos, Olesen, & Rasmussen, 2015, demonstrated that an exercise therapy associated with patient' load management education had long term (24 months) positive effect on reducing pain and improve overall function in adolescents with PFP.…”
Section: Discussionmentioning
confidence: 93%
“…Most of the exercise trials in PFP focus their outcomes in patient-reported measures, not in objective measures 18,19 . Subjective and objective outcomes have different constructs 20 , therefore understanding the effect of a comprehensive exercise program in the objective function of women with PFP is a novel addition into PFP literature.…”
Section: Introductionmentioning
confidence: 99%